Impact of sarcopenia on long-term mortality and cardiovascular events in patients undergoing hemodialysis - Kim, Jwa-Kyung; Kim, Sung Gyun; Oh, Ji-Eun; Lee, Young-Ki; Noh, Jung-Woo; Kim, Hyung Jik; Song, Young Rim (The Korean journal of internal medicine, 2019)
A high body mass index (BMI) is known to correlate with better survival in patients on hemodialysis (HD). However, the impacts of body composition and sarcopenia on survival have not been well studied in this population. One hundred and forty-two prevalent HD patients were recruited and followed prospectively for up to 4.5 years. Low muscle mass (measured using a portable, whole-body, bioimpedance spectroscopic device) was defined as a lean tissue index (LTI) two standard deviations (SD) or more below the normal gender-specific mean for young people. Low muscle strength was a handgrip strength (HGS) of less than 30 kg in males and less than 20 kg in females. Sarcopenia was considered present when both LTI and HGS were reduced. The mean age was 59.8 ± 13.1 years; 57.0% were male and 47.2% had diabetes. Forty-seven patients (33.1%) had sarcopenia. During follow-up, 28 patients (19.7%) died, and low LTI (adjusted hazard ratio [HR], 2.77; 95% confidence interval [CI], 1.10 to 6.97) and low HGS (HR 5.65; 95% CI, 1.99 to 16.04) were independently associated with mortality. Sarcopenia was a significant predictor for death (HR, 6.99; 95% CI, 1.84 to 26.58; p = 0.004) and cardiovascular events (HR, 4.33; 95% CI, 1.51 to 12.43; p = 0.006). Sarcopenia was strongly associated with long-term mortality and cardiovascular events in HD patients. Assessment of muscle strength and muscle mass may provide additional prognostic information to survival in patients with end-stage renal disease.